RESULTS OF EXPERIMENTAL RESEARCH OF HYDRODYNAMICS OF A STATIONARY LAYER DURING FILTRATION DRYING OF RAW COTTON - Khussanov Alisher Ye,; Atamanyuk Volodimir M.,; Kaldybayeva Botagoz M.,; Abilmagzhanov Arlan Zh.,; Janabayev Dauren Zh.,; Khussanov Zhakhongir Ye, (Scientific Journal of Pedagogy and Economics, 2020)
This article presents the results of experimental researches of the hydrodynamics of a stationary layer during filtration drying of raw cotton. At the same time, the total energy consumption for the process of filtration drying consists of pressure losses in the stationary layer and heating of the heat agent to a predetermined temperature. For this, it is important to establish the dependence of pressure losses in a stationary layer of wet cotton fiber on the fictitious filtration rate of the heat agent, as an important factor determining the intensity and economic efficiency of filtration drying. All experiments were carried out with appropriate hangings of cotton fiber, taking into account that the natural moisture content of cotton fiber is insignificant. Experimental studies have been conducted on filtering a thermal agent through a conditionally stationary layer of cotton fiber with different weights were performed in the form of a functional dependence ∆Р = f (ݒ .(଴The results of comparing the ratio of experimentally determined values of pressure losses in a conditionally stationary layer of cotton fiber to those theoretically calculated as a function of the Reynolds number are presented. The absolute value of the relative error does not exceed 14.2%, which is explained by the complex structure and spontaneity of the formation of a stationary layer of cotton fiber, as well as the impact of the pressure drop on the height of the layer.